Krisis integritas generasi muda: Urgensi pendidikan anti korupsi dalam dunia pendidikan - Salsabila, Shabrina Arinza (Maliki Interdisciplinary Journal, 2026)
A crisis of integrity among the younger generation is beginning to emerge in educational settings, as evidenced by cheating and a lack of transparency in administrative activities. These phenomena indicate a decline in the values of honesty and responsibility, thereby fostering a culture of corruption from an early age. This study aims to examine the urgency of anti-corruption education in shaping the character of the younger generation with integrity. The method used is a literature review, examining various scientific sources related to anti-corruption education and the integrity crisis among the younger generation. The results of the study indicate that anti-corruption education plays a crucial role in instilling moral values. However, the implementation of this education still faces challenges in the form of a pragmatic culture, a lack of role models, and the influence of digital technology Therefore, anti-corruption education requires strengthening through collaboration among schools, families, and the community to foster a generation of youth with strong character and integrity.